ANALISIS KETERAMPILAN BERBICARA AWAL SISWA KELAS IV DI SDN WANASARI 13 - Larasati, Anggi; Amelia, Decenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to describe the initial speaking skills of fourth-grade students at SDN Wanasari 13 Cibitung, Bekasi Regency, in the 2024/2025 academic year. This study was conducted using a descriptive qualitative approach. Data in this study were obtained from teachers and fourth-grade students. Data were collected using observation techniques, informal interviews with teachers, and oral tests. The results obtained revealed that most students still have low initial speaking skills, both in terms of word choice (diction), intonation, fluency, use of facial expressions and gestures, and reasoning. This condition indicates the need for more supportive treatment or learning approaches, such as project-based learning, role-playing, simple interviews, adlibbing methods (spontaneous speaking), and the use of media such as podcasts and audiovisuals can also be applied as innovative and fun learning approaches. This study is expected to provide a basis for designing more effective methods or approaches to speaking learning at the elementary school level.